2015
DOI: 10.1016/j.neo.2015.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Progenitor Cell Dysfunction in Myelodysplastic Syndromes: Possible Contribution of a Defective Vascular Niche to Myelodysplasia

Abstract: We set a model to replicate the vascular bone marrow niche by using endothelial colony forming cells (ECFCs), and we used it to explore the vascular niche function in patients with low-risk myelodysplastic syndromes (MDS). Overall, we investigated 56 patients and we observed higher levels of ECFCs in MDS than in healthy controls; moreover, MDS ECFCs were found variably hypermethylated for p15INK4b DAPK1, CDH1, or SOCS1. MDS ECFCs exhibited a marked adhesive capacity to normal mononuclear cells. When normal CD3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 49 publications
(53 reference statements)
0
35
0
Order By: Relevance
“…36 In fact, multiple reports identify endothelial dysfunction in patients with MDS. [37][38][39][40][41] Therefore, although further studies are required to confirm that the three-dimensional architecture of this murine model approximates that found in human MDS, the NHD13 model is likely to faithfully replicate the BMME changes initiated by at least some subsets of human MDS. The clinical relevance of our murine model is also supported by the increase in VEGF, similar to what is reported in human MDS.…”
Section: Blood 4 February 2016 X Volume 127 Number 5 the Marrow Micmentioning
confidence: 99%
“…36 In fact, multiple reports identify endothelial dysfunction in patients with MDS. [37][38][39][40][41] Therefore, although further studies are required to confirm that the three-dimensional architecture of this murine model approximates that found in human MDS, the NHD13 model is likely to faithfully replicate the BMME changes initiated by at least some subsets of human MDS. The clinical relevance of our murine model is also supported by the increase in VEGF, similar to what is reported in human MDS.…”
Section: Blood 4 February 2016 X Volume 127 Number 5 the Marrow Micmentioning
confidence: 99%
“…The results of these studies provided evidence that the number of both CECs and ECFCs is consistently increased in MDSs (81,82). Particularly, Dalla Porta and coworkers observed an increased number of CECs, their number being positively correlated with bone marrow MVD and negatively correlated with the international prognostic scoring system risk (81).…”
Section: Angiogenesis In Myelodysplastic Syndromesmentioning
confidence: 97%
“…Intriguingly, these authors showed that a variable, but significant proportion of CECs display the same chromosome abnormalities detected at the level of the hematopoietic cells (81). Teofili and coworkers observed that the levels of ECFCs is markedly increased in low-risk MDS patients, compared to normal controls (82); furthermore, ECFCs derived from MDSs display several epigenetic abnormalities and were less competent than those derived from normal controls to support normal hematopoiesis from CD34 + cells (82).…”
Section: Angiogenesis In Myelodysplastic Syndromesmentioning
confidence: 99%
“…These ECFCs showed a marked adhesive capacity to normal mononuclear cells, had lower ability to generate CD11b + CD41 + cells after co-culture with CD34 + HSCs than their normal counterparts, expressed a high level of genes involved in cell adhesion and hypo-expressed various miRNAs involved in Wnt pathway regulation (98). Della Porta et al found an increased number of circulating ECs in MDS cases with increased BM angiogenesis, and this parameter correlated inversely with the IPPS score (97).…”
Section: Stromal Cell Deficienciesmentioning
confidence: 99%